A new Middle Jurassic caddisfly (Trichoptera, Hydrobiosidae) from China. Issue 1 (21st February 2013) - Gao, Yan; Yao, Yunzhi; Ren, Dong
Abstract Material belonging to a new fossil genus and species of caddisfly, Pulchercylindratus punctatus n. gen., n. sp., was collected from the Daohugou locality (Middle Jurassic, Jiulongshan Formation; Inner Mongolia, China). The new species is assigned to the Hydrobiosidae according to subcylindrical shape of the 2nd segment of maxillary palp, the forked R1 (in the forewing, located near apex), and long anal cells (in the forewing). In addition, we propose to transfer the genus Juraphilopotamus Wang, Zhao & Ren 2009, known from the same locality, to the family Hydrobiosidae, based on the 1st and 2nd segments of the maxillary palp being cylindrical, shorter than the 3rd segment. A Middle Jurassic origination of family Hydrobiosidae can be established based on the new discovery. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)